Prospective evaluation of radiographic manifestations of tuberculosis in relationship with CD4 count in patients with HIV/AIDS. Issue 7 (17th February 2023) - Frey, Vanessa; Phi Van, Valerie Doan; Fehr, Jan S; Ledergerber, Bruno; Sekaggya-Wiltshire, Christine; Castelnuovo, Barbara; Kambugu, Andrew; Bauer, Max; Eberhard, Nadja; Martini, Katharina; Frauenfelder, Thomas
Abstract : A major risk factor to develop active tuberculosis (TB) is the infection with the human immunodeficiency virus (HIV). Chest radiography is the first-line imaging modality used to rule out TB. Coinfected individuals present often with atypical imaging patterns, due to the immunosuppression caused by the virus, making diagnosis difficult. In this prospective observational study 268 TB and HIV coinfected patients were included. During a follow-up period of 24 weeks, the predominant patterns on chest radiography were analyzed and compared to the cluster of differentiation 4 (CD4) count under antiretroviral and anti-TB therapy. Patients with low CD4 counts (<200 cells//µL) showed more often lymphadenopathy (62% vs 38%; P = .08) and a miliary pattern (64% vs 36%; P = .04) but less likely cavitation (32% vs 68%; P = .008) or consolidation (47% vs 63%; P = .002) compared to individuals with higher CD4 counts. Over the follow-up period, partial response to therapy was the most frequent radiological evolution (62%), mainly accompanied by an increase of CD4 cells (92%). Patients with a decrease in CD4 count mostly presented with a worsening in radiological findings (53%). Radiographic TB manifestation correlated with the immune status of patients coinfected with HIV. Low CD4 counts often showed atypical manifestation.